Reliable and energy-efficient cooperative OFDM communications over underwater acoustic channels - Cheng, Xilin, author; Yang, Liuqing, advisor; Azimi-Sadjadi, Mahmood R., committee member; Luo, J. Rockey, committee member; Wang, Haonan, committee member (Colorado State University. Libraries, 2015)
Underwater acoustic sensor networks (UWASN) have been attracting growing research interests in recent decades due to various promising applications. Underwater acoustic communications (UAC), which adopts acoustic waves as the information carrier, is one of the key communication techniques to realize UWASN. However, UAC is very challenging due to low carrier frequency, distance-dependent bandwidth, large delay spread, long and variable propagation delay, and doubly-selective fading. In this research, we will consider cooperative communications to improve the reliability and energy efficiency of dual-hop UAC. OFDM is adopted as the physical-layer transmission technique. First, we will examine power allocation issues. Two transmission scenarios are considered, namely short-range transmission and medium-long range transmission. For the former scenario, an adaptive system is developed based on instantaneous channel state information (CSI); for the latter scenario, an selective relaying protocol is designed based on statistical CSI. Secondly, we will focus on the decomposed fountain codes design to enable reliable communications with higher energy efficiency. Finally, to improve the packet transmission reliability, data repetition within one or two consecutive OFDM symbols is implemented according to the mirror-mapping rules. Theoretical analyses and simulation results demonstrate that the reliability and energy efficiency of dual-hop UAC can be substantially improved using the aforementioned techniques.
Keywords: cooperative communications; energy efficiency; OFDM; reliability; underwater acoustic communications